“It Was All that I Could Think of.” Migration, Youth, and Folkloric Entertainment in Rural Romania - COSMA, Valer Simion; CONSTANTINIU, Theodor (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
Abstract: A hybrid that originated in the traditional peasant music, Romanian popular music (muzică populară), as it is known from radio broadcasts, TV shows or live performances from all around the country, was developed by mixing the village music of the twentieth century with techniques and principles borrowed from the classical repertoire and other light genres. Muzica populară emerged in the interwar years, but was perfected and regulated by the communist regime, becoming one of the favorite genres of the rural and urban working class and, nowadays, it continues to have a great appeal among all age categories. Our aim was to discover the motivations that lead the village youth of Romania to involve themselves in activities dealing with muzica populară, in particular, or with folklore and traditions, in general. To accomplish this, we conducted several interviews with young people from Sălaj county, from which a few patterns emerged: the rapid familiarization with the genre due to specific TV channels; the acquired taste due to grandparents raising their grandchildren in the absence of the parents who migrated in the 2000s; the expressed devotion to the local culture and their willingness and duty to preserve and promote it. We can also explain the success of muzică populară among young people by structural factors that are at work in the whole society, namely the lack of interest of post-communist authorities in building and/or maintaining a cultural and educational infrastructure in the rural areas. Thus, this paper aims to explore contemporary rural pop culture by considering the connection between the deterioration of the cultural infrastructure in rural areas, transnational migration and the exponential development of an industry devoted to the recent muzică populară.